ANALISIS FLUKTUASI HARGA SAHAM BLUE CHIPS DENGAN MENGGUNAKAN ALGORITMA C4.5 - Yohanes Leonardus Dwi Pradipta; Desi Arisandi; Tri Sutrisno (Fakultas Teknologi Informasi Universitas Tarumanagara, 2022)
In this digital era, the development of stock investment has been fairly rapid and has begun to be used as a source of livelihood for some people, especially during the pandemic. However, for some people who are not familiar with stocks, they will find it difficult to make a decision to make transactions in the stock market. Because in the stock itself, there are several categories based on their quality, ability, and reliability in various situations. With this problem, a thesis was made with the title